MINERAL COMPOSITION AND PT PARAMETERS OF CRYSTALLIZATION OF MANTLE ROCKS UNDER KIMBERLITE FIELDS OF THE ANABAR REGION - S. I. Kostrovitsky; T. V. Kalashnikova; I. V. Ashchepkov (Геодинамика и тектонофизика)
The composition of barophilic minerals from mantle xenoliths and Cpx from concentrates of the Kuranakh, Luchakan, Dyuken, and Ary-Mastakh fields of the Anabar region has been studied. Under these fields, the lithospheric mantle compositions vary significantly. The PT parameters of crystallization were calculated using the composition of clinopyroxenes from xenoliths and heavy fraction of kimberlites. The lithospheric mantle rocks under the northern fields have higher values of Mg# of minerals and calculated mantle geotherm (35–48 mW/m2) compared to the parameters for the southern diamond fields. The pipes from the southwestern part of the Ary-Mastakh field are promising for the diamond potential, presenting Grt-bearing lherzolites and harzburgites with a high content of Cr2O3 (to 8.5 wt. %).